Coupling effects of water availability and pH on switchgrass and the optimization of these variables for switchgrass productivity determined by response surface methodology. (December 2015) - Zhang, Hongjuan; Wang, Quanzhen; Liu, Yuan; Cui, Jian; Ma, Xiaomin; Gu, Muyu; Xia, Maolin
Abstract: Perennial grasses can be planted in marginal lands, and the perennial grass species switchgrass ( Panicum virgatum ) has emerged as an ideal candidate for bioethanol production. To choose the optimal soil water content and pH value for bioethanol production using switchgrass, a greenhouse experiment was conducted with five pH levels (4.9, 6.3, 7.0, 7.7, and 9.1) and five soil water contents (8%, 16%, 20%, 24%, and 32%). The coupling effects of water and pH stresses on switchgrass were investigated by evaluating fresh weight and dry weight, biomass composition (acid detergent fiber, neutral detergent fiber, acid detergent lignin, cellulose, hemi-cellulose, and lignin) and physiological response (soluble sugar content, proline content, MDA content, chlorophyll content and relative conductivity) in Alamo switchgrass. The results demonstrate a significant and positive correlation between the cellulose and acid detergent fiber content in switchgrass biomass (R 2 = 0.959). The results of the variance analyses demonstrate that water and pH stress yielded a coupling effect on switchgrass, and this finding was significant for fresh weight and neutral detergent fiber and proline content. By response surface methodology, the optimal combination of soil water content (SWC) and pH was SWC = 31.968%–44.424% and pH = 6.328–8.123. These results provide basic evidence for planting switchgrass in marginal lands. Highlights: Orthogonal rotation design methods are used to optimize the coupling effect of water and pH stress. Effects of water and pH stress on plant productivity in switchgrass are investigated. The water and pH stresses yield a coupling effect on switchgrass. Optimal combination of soil water content and pH is determined.